EVALUASI INTERAKSI DAN KETEPATAN PENGATURAN JADWAL OBAT UNIT DOSE DISPENSING PASIEN RAWAT INAP SALAH SATU RUMAH SAKIT DI KOTA BANDUNG PERIODE FEBRUARI 2022: EVALUATION OF INTERACTIONS AND ACCURACY OF ARRANGEMENTS THE UNIT-DOSE DISPENSING DRUG SCHEDULES INPATIENTS IN HOSPITAL AT BANDUNG CITY IN FEBRUARY 2022 - Yovita Mercya; Ifvana Pricialiany; Lanang Eko Sampurno Sampurno (Jurnal Kesehatan, 2023)
Unit Dose Dispensing (UDD) is drug distribution for one dose per patient. UDD can reduce drug interactions because pharmacists monitor it. This study aims to determine the percentage of drug interactions related to scheduling, the severity of interactions, and the most drug interaction pairs. This type of research is observational study conducted retrospectively using purposive sampling of prescriptions and UDD Medication List inpatients at one of hospital in Bandung city in February 2022 and analyzed quantitatively-descriptively. Data processing using drug interaction checker software. Data analyzed based on the incidence of drug interactions, the accuracy of scheduling, the severity, and the most drug interaction pairs. The results were still found drug interactions in 73 patients (43,98%) (n=166) consisting of 194 drug interactions, 113 events (58.25%) the UDD schedule were correct and 81 events (41.75%) were not. Based on the severity level, in all prescriptions with drug interactions, the moderate level was 63.40%, the minor level was 25.26%, and the mayor level was 11.34%. Meanwhile, in 81 events with incorrect schedule, the moderate level was 52 events (64.20%), the minor level was 19 events (23.46%), and the mayor level was ten events (12.35%). The most common interaction was aspirin-clopidogrel with moderate severity.